FACTORS AFFECTING COPPER REMOVAL FROM SIMULATED WASTEWATER USING RICE HUSK ASH AS AN ADSORBENT - Imran, Kashif; Ahmed, Dildar; Zahra, Naseem (International Journal of Research -GRANTHAALAYAH, 2016)
The present study entails the effect of various factors affecting removal of copper from simulated wastewater by using rice husk ash as an adsorbent. Various standard solutions of copper nitrate were prepared and treated with rice husk ash (RHA) to investigate adsorption on the adsorbent under different conditions of pH, temperature, time and adsorbate dose. Maximum removal of Cu2+ was observed at its low concentration of 10 ppm at 50 ˚C and 90 minutes contact time. The percentage adsorption decreased with increase in concentration of Cu2+. The removal of 30 ppm and 40 ppm Cu2+ solutions was maximum at pH 6 and 8, respectively. It was concluded that RHA can be used for Cu2+ removal from wastewater containing copper ions by suitably optimizing the conditions.